Face-name Associative Memory Performance is Related To Amyloid Burden in Normal Elderly - Rentz, Dorene M. (2011)
Cerebral amyloid beta (Aβ) deposition occurs in a substantial fraction of cognitively normal (CN) older individuals. However, it has been difficult to reliably detect evidence of amyloid-related cognitive alterations in CN using standard neuropsychological measures. We sought to determine whether a highly demanding face-name associative memory exam (FNAME) could detect evidence of Aβ-related memory impairment in CN. We studied 45 CN subjects (mean age = 71.7 ± 8.8) with Clinical Dementia Rating (CDR) scores = 0 and MMSE ≥ 28, using Positron Emission Tomography with Pittsburgh Compound B (PiB PET). Memory factor scores were derived from a principal components analysis for FNAME name retrieval (FN-N), FNAME occupation retrieval (FN-O) and the 6-Trial Selective Reminding Test (SRT). Using multiple linear and logistic regression analyses, we related the memory factor scores to PiB distribution volume ratios (DVR, cerebellar reference) as either a continuous or a dichotomous variable in frontal cortex and a posterior cortical region representing the precuneus, posterior cingulate and lateral parietal cortices (PPCLP), co-varying for age and AMNART IQ (a proxy of cognitive reserve (CR)). A significant inverse relationship for FN-N was found with Aβ deposition in frontal (R(2) = .29, β = −2.2, p = 0.02) and PPCLP cortices (R(2) = .26, β = −2.4, p = 0.05). In contrast, neither FN-O nor the SRT were significantly related to Aβ deposition. Performance on a demanding test of face-name associative memory was related to Aβ burden in brain regions associated with memory systems. Associative memory for faces and names, a common complaint among older adults, may be a sensitive marker of early Aβ-related impairment.